Penguatan Wawasan Kebangsaan bagi Mahasiswa Melalui Mata Kuliah Pancasila - Muhamad Baedowi; Lilik Kartika Sari (Journal on Education, 2023)
This research discusses the importance of strengthening national insights for students through early childhood education courses. Where these courses are mandatory subjects for tertiary institutions in Indonesia. The approach in this study is a qualitative descriptive approach using observation, documentation and interview techniques. The results of this study of 576 respondents were that 33.9% of students answered that they agreed with the existence of the caliphate and 68.6% of students disagreed with the existence of the caliphate, 0.5% of students agreed with the existence of suicide bombings and 99.5% did not agree with this action. Furthermore, 0.2% of students answered that they agreed with acts of terrorism and 99.8% did not agree with these actions. As well as the existence of banned organizations on campus that are affiliated towards radicalism by 5% and 95% of other students answered none. Therefore, most students (94.3%) agree with the strengthening of nationalism and 6.3% of students disagree with strengthening nationalism.